Varicocoele embolization with sclerosing agents leads to lower radiation exposure and procedural costs than coils: Data from a real‐life before and after study. (26th February 2022) - Boeri, Luca; Fulgheri, Irene; Cristina, Marco; Biondetti, Pierpaolo; Rossi, Silvia; Grimaldi, Elena; Lucignani, Gianpaolo; Gadda, Franco; Ierardi, Anna Maria; Salonia, Andrea; Viganò, Paola; Somigliana, Edgardo; et al.
Abstract: Objectives: To investigate clinical outcomes, radiation exposure and procedural costs associated with percutaneous varicocoele embolization using coils and sclerosing agents (SAs) in a cohort of young‐adult men. Materials and methods: Data from consecutive men treated with percutaneous varicocoele embolization using coils and SA between 2017 and 2021 were analyzed. The allocation was based on a change of policy occurred in June 2020 with the substitution of coils with SA (before and after study). Semen analysis values were based on 2010 WHO reference criteria. Anatomic variants of gonadal veins were categorized according to Jargiello et al. Intraoperative radiation dose and procedural costs were collected for each patient. Descriptive statistics and linear regression models were used to describe the association between clinical parameters with procedural costs and radiation exposure. Results: One hundred sixteen men were included, of whom 76 (65.5%) received coils, and 40 (34.5%) received SA. Baseline characteristics of the two study groups did not differ. A type 3 Jargiello anatomic variation of left gonadal vein was found in 45.7% of cases. Radiation dose was lower in the SA group as compared to the coils one (13.2 [7–43] vs. 19.8 [12–57] Gy/cm 2 ; p  < 0.001). Similarly, procedural costs were lower for the SA group (169.6 [169–199] € vs. 642.5 [561–775] €; p  < 0.001). At follow‐up, pain and sperm variables significantly improved in both groups ( p  < 0.01), without differences among the embolic materials. Linear regression model revealed that coils use was associated with higher radiation exposure (beta 8.8, p  = 0.02) than SA after accounting for anatomic variation of gonadal vein, body mass index, and vascular access. Conclusions: SA and coils for varicocoele embolization are equally safe and effective. The use of SA was associated with lower radiation exposure and procedural costs than coils. These results should be considered in terms of public health cost and patient's safety.